(untitled) (Global Journal of Human-Social Science, 2020)
Digital technology has an impact on transforming the culture of the youths into online. Such an effect has been captured and mirrored in theatre works that have led to emerging a new genre called posthuman drama. In The Sugar Syndrome (2003), Lucy Prebble offers posthuman themes, posthuman landscape, and cyberfriends. She problematizes the concept of online existence with its result of online culture by blurring the lines between actual life and virtual life represented through electronic and actual connections between a teenager, Dani, and the two men, Lewis and Tim, she meets online. Consequently, and drawing on theories of posthumanism, this study provides an analysis of the play regarding the nature of the relationship between humans and digital machines as well as the conflicts between the physical world and the online world. Psychic agonies related to issues like eating disorders, mental instability, pedophilia, incest, and rape are also explored here through examining cyborg as well as physical encounters between the protagonists.